A baby chooses to emerge out from the posterior cervical tear in a prostaglandin induced labor - Gurung, Geeta; Amatya, Sapana; Amatya, Archana; Rana, Akanchya; Rana, Ashma; Kafle, Akinchan (Nepal Journal of Obstetrics and Gynaecology, 2014)
A case is described where a live baby chooses to come out, tearing apart the posterior cervix as a result of effective uterine contractions in association with closed external cervical os in a prostaglandin E2 induced, postdated pregnancy in a primigravida with neonatal survival. DOI: http://dx.doi.org/10.3126/njog.v3i2.10835 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 57-58